Unpacking public sentiment toward the government: How government communication strategies affect public engagement, cynicism, and word of mouth behavior in South Korea - Soojin KIM, (Institutional Knowledge at Singapore Management University, 2016)
This study tests therelationships between two types of public sentiment toward the government, theirantecedents and their outcomes. A Web survey was conducted in South Korea(N=1112) to understand publics’ evaluations of their sentiments toward thegovernment. The results show that perceived type of government communicationstrategy affects public engagement, public cynicism, and publics’ positive andnegative word of mouth behavior about government. Theoretical and empiricalimplications are discussed.